Income Distribution and Tax Structure: Microeconomic Test of the Meltzer-Richard Hypothesis - Lars-Erik Borge; Jørn Rattsø (Center for Economic Studies and ifo Institute (CESifo), 2001)
The tax structure is important for the income distribution and therefore a key playground for redistributive politics. The standard theory assumes that more unequal income distribution will create a majority for more redistribution (Meltzer and Richard). This study investigates the empirical validity of this relationship in a microeconomic study of the tax structure in decentralized government in Norway. The choice of revenue instruments studied involves user charges and property taxes oriented towards housing. While user charges act as head taxes, property taxes have distributive consequences. The approach is in the tradition of majority rule, and we show how the local government decisions regarding tax structure and spending level can be understood as one-dimensional. This motivates the empirical analysis where the actual income distribution is measured by the ratio of median to mean income. The estimated model confirms that more equal income distribution implies a shift in the tax burden from property taxes to user charges.
Keywords: 330